Eficiência de estirpes de rizóbio no rendimento e qualidade fisiológica de sementes de feijão-caupi (Vigna unguiculata L. Walp.) - Soares, Cláudio Silva (2007)
The use of practices of low impact, as the inoculation of bacteria fixadoras of atmospheric nitrogen, it has been contributing for elevating the productivity of the bean caupi in some producing areas. The objective of the work was to evaluate the efficiency of Rhizobium strains in the production and physiologic quality of cowpea seeds, to cultivate "Corujinha". The research consisted of evaluation of the efficiency of Rhizobium strains and her influence in the production and quality of seeds (Chapter I); influence of those strains in the absorption of nutrients (Chapter II) and, agronomic evaluation of the Rhizobium strains and her influence in the production and quality of seeds (Chapter III). The same treatments were used in the different times of planting of the culture (2005 and 2006) in Neossolo Regolítico. DBC was used with four repetitions, being the treatments: Rhizobium strains (BR 3301, BR 3302, BR 3267, BR 3299 and BR 3262); nitrogen fertilizer (50 kg ha-1; 80 kg ha-1), and control (without inoculation and without N). The portions had 24 m2, with plants spaced in 0,5m x 0,5m, with three plants for hole and useful area of 6 m2. The results were submitted to the variance analysis with averages compared by the test of Scott-Knott to 5%. As for the productivity, a similar development was verified among the strains no recommended officially (BR 3262 and BR 3299) and those already suitable as official strains for the cowpea, however without differing of the fertilized treatments (80 and/or 50 kg ha-1) with N, in the two years of planting. The best ones percentile of germination they were observed with the use of the strains BR 3301 and BR 3302, in the two planting times. The plantules came more vigorous (mass dries of plantules) when originating from big seeds. The absorption of nutrients (NPK) in the plants inoculated by strains was similar that reached by plants fertilized with mineral nitrogen (50 and 80 kg ha-1) and to the treatment it controls. The native strains (it controls) they presented similar acting of the inoculated strains in the two years of cultivation of the cowpea.